2022
DOI: 10.1108/jmd-05-2022-0112
|View full text |Cite
|
Sign up to set email alerts
|

The influence of socio-cognitive mindfulness and resilience on middle managers' stress and thriving during COVID-19: results from two studies

Abstract: PurposeThe purpose of this study was to examine the influence of socio-cognitive mindfulness on resilience, stress and thriving among middle managers in higher education at two separate periods during the COVID-19 pandemic. In Study 1, the authors examined how socio-cognitive mindfulness predicted perceived stress and whether the relationship between mindfulness and perceived stress was mediated by resilience. In Study 2, the authors replicated the first study and further hypothesized that the link between min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 89 publications
(189 reference statements)
1
5
0
Order By: Relevance
“…The findings of this study are also consistent with the empirical demonstrations that have shown the positive relationship between mindfulness and hedonic and eudaimonic well-being (e.g. Slaymaker et al, 2023). The MMT (Garland et al, 2014) developed a background to demonstrate how mindfulness could improve well-being.…”
Section: Theoretical Implicationssupporting
confidence: 89%
See 1 more Smart Citation
“…The findings of this study are also consistent with the empirical demonstrations that have shown the positive relationship between mindfulness and hedonic and eudaimonic well-being (e.g. Slaymaker et al, 2023). The MMT (Garland et al, 2014) developed a background to demonstrate how mindfulness could improve well-being.…”
Section: Theoretical Implicationssupporting
confidence: 89%
“…Mindfulness practices enhance well-being through several key mechanisms. Sociocognitive mindfulness has been shown to improve both forms of well-being as it creates flexibility (Slaymaker et al, 2023) and helps individuals regulate their attention and emotions through reappraisal techniques (Turcotte et al, 2022). Furthermore, mindfulness may enhance individuals' well-being as it improves their consciousness towards daily microevents (daily hassles and daily uplifts) which makes them adjust their affective and behavioral reactions to the situations at hand (Junça- ; in other words, more mindful individuals can easily cope with daily hassles and appear to get the greatest benefit of daily uplifts as they can savor them in the moment of its occurrence (Junça Silva, 2022).…”
Section: Socio-cognitive Mindfulness With Managersmentioning
confidence: 99%
“…WT induces a sense of vitality that brings a feeling of aliveness at work that translates to a sense of attachment to the workplace and a desire for more learning and acquisition of greater skills needed to perform at work (Usman et al, 2023). Furthermore, Slaymaker et al (2023) reported that managers that reported high levels of WT were the most resilient individuals in terms of coping with stressful events. Empirical evidence also indicates that WT influences positive organizational outcomes such as organizational citizenship behavior, innovative work behavior, work engagement, job satisfaction, lower absenteeism and low turnover intentions (Abid and Contreras, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…, 2023). Furthermore, Slaymaker et al. (2023) reported that managers that reported high levels of WT were the most resilient individuals in terms of coping with stressful events.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To explore this possibility, Slaymaker et al . (2023) conduct two similar studies one year apart during the pandemic.…”
Section: Study Evidence From the Usamentioning
confidence: 99%